Transitividade no vocabulário acadêmico em Português Brasileiro: uma análise baseada em artigos científicos - Monique Vieira Miranda (2021)
The present research aimed to analyze the TRANSITIVITY system in the most frequent academic verbs in scientific research articles from different disciplines, accordingly to Nation's (2001) and Webb and Nation's (2017) proposal of vocabulary division and to Systemic-Functional Linguistics (LSF), mainly Halliday and Matthiessen (2014). In addition, various Corpus Linguistics tools were employed, such as #LancsBox (BREZINA et al., 2018) and KitConc (MOREIRA FILHO, 2008). The present work aimed to compile a corpus representative of the genre, in order to build the two central parts of the research: one in which verbs belonging to the academic vocabulary are identified, resulting in the creation of a list of academic verbs, frequent in scientific articles; and another in which the TRANSITIVITY system, inherent to the verbal lemas identified in this list is analyzed, from the perspective of LSF. Based on these goals, we complied a corpus with approximately 12.3 million words of scientific research articles from all the CNPq's Major Areas which provided a variety of linguistic samples sufficient to identify the different vocabulary categories (general, academic, technical and low frequency), especially academic vocabulary. For this purpose, a series of internal and external criteria (GARDNER; DAVIES, 2014; COXHEAD, 2000) were applied to the corpus in order to identify academic verbs in scientific articles in Brazilian Portuguese. Within the scope of LSF, the TRANSITIVITY system refers to the way the user represents and organizes his ideas through language, related to basic sentence organization, whose elements are processes (verbs), participants and circumstances. The analysis from this perspective allowed us to observe that the choices of the types of processes, associated with the configuration of the sentence and of its participants, directly reflect the characteristics of the academic genre, and of the Great Areas in which they occur, such as impersonality in writing, the focus on research activities / procedures and objectivity in reporting analysis and results. Thus, the combination of the two parts of the research, plus the final products - the compiled corpus, which will be made available online, the list of academic verbs and the description of the TRANSITIVITY system - contribute to a deeper understanding on academic writing, advancing in theoretical studies from both areas based on real samples of the language in use.